Оцінка ризику виникнення природжених вад розвитку серед новонароджених Львівської області за період 2002-2012 років - Геник-Березовська, С.О. (Фактори експериментальної еволюції організмів, 2013)
Aims. The analysis of prenatal risks factors among womens, which gave birth to newborns with congenital malformations and control groups in Lviv district during 2002–2012 was carried out. Methods. Analysis of clinical-epidemiological and medical-statistics datas in medical documentations from maternities hospitals of Lviv district using «case-control» method was carried out. Results. The statistically significant increase (Р<0,05) in stillborns (2,8 %) among mothers of examined group comparatively to control group (0,27 %) was revealed. Conclusions. Genetic monitoring of congenital malformations could estimate level of hereditary pathology among newborns and prevent risk factors of it’s origin in population.

Key words: epidemiology, congenital malformations, genetic monitoring, newborns.